SARS-CoV-2 nsp1: Bioinformatics, Potential Structural and Functional Features, and Implications for Drug/Vaccine Designs - Min, Yuan-Qin; Mo, Qiong; Wang, Jun; Deng, Fei; Wang, Hualin; Ning, Yun-Jia (Frontiers in Microbiology, 2020)
The emerging coronavirus disease (COVID-19) caused by SARS-CoV-2 has led to social and economic disruption globally. It is urgently needed to understand the structure and function of the viral proteins for understanding of the viral infection and pathogenesis and development of prophylaxis and treatment strategies. Coronavirus nonstructural protein 1 (nsp1) is a notable virulence factor with versatile roles in virus-host interactions and exhibits unique characteristics on sequence, structure, and function mode. However, the roles and characteristics of SARS-CoV-2 nsp1 are currently unknown. Here, we analyze the nsp1 of SARS-CoV-2 from the following perspectives: 1) bioinformatics analysis reveals that the novel nsp1 is conserved among SARS-CoV-2 strains and shares significant sequence identity with SARS-CoV nsp1; 2) structure modeling shows a 3D /β-fold of SARS-CoV-2 nsp1 highly similar to that of the SARS-CoV homologue; 3) by detailed, functional review of nsp1 proteins from other coronaviruses (especially SARS-CoV) and comparison of the protein sequence and structure, we further analyzed the potential roles of SARS-CoV-2 nsp1 in manipulating host mRNA translation, antiviral innate immunity and inflammation response and thus likely promoting viral infection and pathogenesis, which are merited to be tested in the future. Finally, we discussed how understanding of the novel nsp1 may provide valuable insights into the designs of drugs and vaccines against the unprecedented coronavirus pandemic.